Analysis of the Long-Lived Responses Induced by Immunostimulants and Their Effects on a Viral Infection in Zebrafish (Danio rerio) - Álvarez-Rodríguez, Margarita; Pereiro, Patricia; Reyes-López, Felipe E.; Tort, Lluis; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2018)
In recent years, the innate immune response has gained importance since evidence indicates that after an adequate priming protocol, it is possible to obtain some prolonged and enhanced immune responses. Nevertheless, several factors, such as the timing and method of administration of the immunostimulants, must be carefully considered. An inappropriate protocol can transform the treatments into a double-edged sword for the teleost immune system, resulting in a stressful and immunosuppressive state. In this work, we analyzed the long-term effects of different stimuli (β-glucans, lipopolysaccharide and polyinosinic:polycytidylic acid) on the transcriptome modulation induced by Spring Viremia Carp Virus (SVCV) in adult zebrafish (Danio rerio) and on the mortality caused by this infection. At 35 days post-immunostimulation, the transcriptome was found to be highly altered compared to that of the control fish, and these stimuli also conditioned the response to SVCV challenge, especially in the case of β-glucans. No protection against SVCV was found with any of the stimuli, and non-significant higher mortalities were even observed, especially with β-glucans. However, in the short term (pre-stimulation with β-glucan and infection after 7 days), slight protection was observed after infection. The transcriptome response in the zebrafish kidney at 35 days post-treatment with β-glucans revealed a significant response associated with stress and immunosuppression. The identification of genes that were differentially expressed before and after the infection seemed to indicate a high energy cost of the immunostimulation that was prolonged over time and could explain the lack of protection against SVCV. Differential responses to stress and alterations in lipid metabolism, the tryptophan-kynurenine pathway and interferon-gamma signaling seem to be some of the mechanisms involved in this response, which represents the end of trained immunity and the beginning of a stressful state characterized by immunosuppression.